HLA*LA—HLA typing from linearly projected graph alignments - Dilthey, AT; Mentzer, AJ; Carapito, R; Cutland, C; Cereb, N; Madhi, SA; Rhie, A; Koren, S; Bahram, S; McVean, G; Phillippy, AM (Oxford University Press, 2019)
Summary HLA*LA implements a new graph alignment model for human leukocyte antigen (HLA) type inference, based on the projection of linear alignments onto a variation graph. It enables accurate HLA type inference from whole-genome (99% accuracy) and whole-exome (93% accuracy) Illumina data; from long-read Oxford Nanopore and Pacific Biosciences data (98% accuracy for whole-genome and targeted data) and from genome assemblies. Computational requirements for a typical sample vary between 0.7 and 14 CPU hours per sample. Availability and implementation HLA*LA is implemented in C++ and Perl and freely available as a bioconda package or from https://github.com/DiltheyLab/HLA-LA (GPL v3).